Determinants of anxiety in elite athletes: a systematic review and meta-analysis. Issue 11 (16th May 2019) - Rice, Simon M; Gwyther, Kate; Santesteban-Echarri, Olga; Baron, David; Gorczynski, Paul; Gouttebarge, Vincent; Reardon, Claudia L; Hitchcock, Mary E; Hainline, Brian; Purcell, Rosemary
Abstract : Objective: To identify and quantify determinants of anxiety symptoms and disorders experienced by elite athletes. Design: Systematic review and meta-analysis. Data sources: Five online databases (PubMed, SportDiscus, PsycINFO, Scopus and Cochrane) were searched up to November 2018 to identify eligible citations. Eligibility criteria for selecting studies: Articles were included if they were published in English, were quantitative studies and measured a symptom-level anxiety outcome in competing or retired athletes at the professional (including professional youth), Olympic or collegiate/university levels. Results and summary: We screened 1163 articles; 61 studies were included in the systematic review and 27 of them were suitable for meta-analysis. Overall risk of bias for included studies was low. Athletes and non-athletes had no differences in anxiety profiles ( d =−0.11, p=0.28). Pooled effect sizes, demonstrating moderate effects, were identified for (1) career dissatisfaction ( d =0.45; higher anxiety in dissatisfied athletes), (2) gender ( d =0.38; higher anxiety in female athletes), (3) age ( d =−0.34; higher anxiety for younger athletes) and (4) musculoskeletal injury ( d =0.31; higher anxiety for injured athletes). A small pooled effect was found for recent adverse life events ( d =0.26)—higher anxiety in athletes who had experienced one or more recent adverse life events. Conclusion: Determinants of anxiety in elite populations broadly reflect those experienced by the general population. Clinicians should be aware of these general and athlete-specific determinants of anxiety among elite athletes.